Mfd deficiency decreases the abundance of complete transcripts of sporulation genes and alters sporogenesis and the structure of dormant Bacillus subtilis spores - Martin, Holly Anne; Heron, Robert; Leyva-Sanchez, Hilda; Perez, Ryan King; Callaway, Amber; Ermi, Tatiana; Picard, Aude; Grifaldo, Jessica; Barnes, Jesse L.; Pedraza-Reyes, Mario; Robleto, Eduardo A. (Frontiers in Microbiology, 2025)
Sporulation is a survival mechanism employed by Firmicutes, including Bacillus subtilis, when facing stressful conditions of growth (e.g., starvation). In this bacterium, the transcription repair coupling factor, Mfd, has been shown to play pivotal roles in sporulation transcription-coupled DNA repair and stress-associated mutagenesis. Recent studies have also revealed an unexpected role of Mfd in regulating gene expression during B. subtilis sporulation. This study examines the effects of B. subtilis Mfd deficiency on the expression of sporulation genes, sporulation efficiency, and spore morphology. In the absence of exogenous DNA damage, we found that Mfd deficiency does not compromise spore germination outgrowth; however, the loss of this factor promoted spore morphological defects and decreased sporulation efficiency. Also, our results confirmed an anomalous pattern of expression of sporulation genes in cells lacking Mfd. These results showed that Mfd influences bacterial physiology beyond DNA repair of actively transcribed genes.